IDENTIFIKASI BENTUK, STRUKTUR DAN PERANAN HUTAN KOTA MALABAR MALANG - Rizki Alfian; Hendra Kurniawan (Universitas Tribhuwana Tunggadewi, 2010)
City of Malang have the number of Green Open Space (RTH) less adequate (0,2 %). From result of total comparison between RTH 171.571 m2 and total wide city region 147.138 km2. As for standard of RTH 5-10% wide of city region. The existing city forest include: (1) Jakarta Street for the area of 2.221 m2 in the area of Penanggungan village, sub -District of Klojen, (2) Forest of Malabar for the area of 16.718 m2 in Sub-District of Oro-Oro Dowo District of Klojen, (3) Garden of Velodrom for the areas of 12.500 m2 in Madyopuro village in Sub District of Kedungkandang. This research activity take about six month. Location of research is in forest town of Malabar Sub-District of Oro-Oro Dowo Sub District of Klojen with areas of 16.718 m2. Research result concluded that structure of city forest of Malabar have strata two because there were only consisting of grass and grove or other ground cover. City forest of Malabar have an good effect function of ecological aspect (76,5 %) with score average 4,52 and have an effect on good enough for the aspect of landscap 81,5% with score average 3,45